Sagittal suture morphological variation in human archaeological populations. Issue 12 (5th April 2021) - Cheronet, Olivia; Ash, Abigail; Anders, Alexandra; Dani, János; Domboróczki, László; Drozdova, Eva; Francken, Michael; Jovanovic, Marija; Milasinovic, Lidija; Pap, Ildiko; Raczky, Pál; Teschler‐Nicola, Maria; et al.
Abstract: Cranial sutures join the many bones of the skull. They are therefore points of weakness and consequently subjected to the many mechanical stresses affecting the cranium. However, the way in which this impacts their morphological complexity remains unclear. We examine the intrinsic and extrinsic mechanisms of human sagittal sutures by quantifying the morphology from 107 individuals from archaeological populations spanning the Mesolithic to Middle ages, using standardized two‐dimensional photographs. Results show that the most important factor determining sutural complexity appears to be the position along the cranial vault from the junction with the coronal suture at its anterior‐most point to the junction with the lambdoid suture at its posterior‐most point. Conversely, factors such as age and lifeways show few trends in complexity, the most significant of which is a lower complexity in the sutures of Mesolithic individuals who consumed a tougher diet. The simple technique used in this study therefore allowed us to identify that, taken together, structural aspects play a more important role in defining the complexity of the human sagittal suture than extrinsic factors such as the mechanical forces imposed on the cranium by individuals' diet.